Oligocene–Miocene arc magmatic activities associated with the giant Reko Diq porphyry Cu–Au deposit, western Chagai arc, Balochistan, Pakistan - Muhammad, Shafi; Liu, Junlai; Ullah, Inayat; Chen, Xiaoyu; Ji, Lie; Zahid, Muhammad Aleem; Kakar, Naseer (Geological journal (Chichester, England), 2024)
The Chagai belt to the north of the Afghan block and the east of the Iranian block in the western part of Pakistan is known for occurrence of Oligocene to Miocene calc‐alkaline magmatic belt. The present study discusses the characteristics of episodic magmatic activities that contributed to mineralization for the Reko Diq porphyry complex in the western part of the Chagai belt. U–Pb dating of zircons from volcanic rocks of the Reko Diq porphyry complex yielded ages of 25.8 ± 1.8 and 12.29 ± 0.44 Ma for two phases of magmatic crystallization. Geochemical analyses of whole‐rock rhyolite and dacite indicate that the rock units are peraluminous calc‐alkaline, derived from Andean‐type subduction. The magma was formed due to partial melting of the thickened mafic lower crust in a continental arc setting in relation to the subduction of the Neotethys along the Makran subduction zone. The abundance of zircons, Hf, REE, U/Pb and Th indicates high degrees of magmatic evolution. Moreover, the Sr and Nd isotopic data indicate the fractional contribution of depleted N‐MORB mantle to the Reko Diq magmas through bulk mixing with magmas derived from the lower continental crust. Short‐lived magmatic systems repeated magma injection, and various episodes of hydrothermal fluid flow have led to the formation of porphyry mineralization. Emplacement of the Reko Diq porphyry complex and related Cu–Au mineralization is associated with a series of tectonic–magmatic events at different episodes of the Oligocene–Miocene times. The Reko Diq porphyry Cu–Au deposit is situated within the western Chagai arc and was formed during the Oligocene–Miocene period. It is associated with granodiorite porphyry deposits and originated from volcanic rocks due to the subduction‐related magmatism. The volcanic rocks and the magma from a common chamber beneath the volcanic basin underwent parallel fractionation processes.